UPAYA MENINGKATKAN MOTIVASI BELAJAR DENGAN IMPLEMENTASI PEMBELAJARAN KOOPERATIF METODE THINK PAIR SHARE SECARA DARING - ali nurdin (MGMP PAI Jawa Barat, 2023)
This classroom action research was conducted to find out how the implementation of the Think Pair Share type cooperative learning model was able to increase student motivation in online learning in Class IX-E at SMP Negeri 14 Cirebon. This research was descriptive qualitative in nature and was conducted in two research cycles with 24 students as participants. The researcher himself acted as a participant-observer in this research. Data collection techniques were carried out through observation and document analysis, and the findings were then analyzed qualitatively based on relevant theories put forward in the research. This research concludes that the implementation of the Think Pair Share type cooperative learning model is able to improve PAI learning outcomes in Class IX-E at SMP Negeri 14 Cirebon. Asking and answering each other develops students' abilities in speaking and critical thinking. However, holding online classes requires maximum effort from teachers in motivating students to take part in learning activities. Technical obstacles still often cause problems in online learning activities. Therefore, further research related to the issues above is still recommended to obtain satisfactory findings.